THE PRIORITY DIRECTIONS OF THE CONTENTS OF THE STANDARD MUSIC CURRICULUM IN THE CONDITIONS OF FORMING AND DEVELOPING OF INDEPENDENT KAZAKHSTAN (1993-2013) - Kulmanova, Sholpan (Pedagogy and Psychology, 2022)
The article reveals the peculiarities of the contents of the standard music curriculum for primary grades developed, experimentally researched and introduced into the educational process of Kazakhstani schools in the 1993-2013 time periods. The author, in the historical aspect, shows the process of working on the contents of the program and corroborates it with factual material. Based on the pedagogical didactic principles, the scientific positions of scholars in the field of psychophysiology and school music education, the program identifies the key knowledge and reveals the optimal conditions for introducing primary school children, in accordance with their age capabilities, to the Kazakh traditional music. The achievable goal of the program was to up bring the younger generation on the best examples of Kazakh traditional musical art, to introduce them to the culture of their people, to form concepts about the role of folk music as a creative source of domestic professional composers and composers of world classics. As a result, contents of standard curriculum were implemented in an educational and methodological complex on music.